The Impact of the Business Environment on Young Firm Financing - Chavis, Larry W.; Klapper, Leora F.; Love, Inessa (2012)
This paper uses a dataset of more than 70,000 firms in over 100 countries to systematically study the use of different financing sources for new and young firms, in comparison to mature firms. The authors find that in all countries younger firms rely less on bank financing and more on informal financing. However, they also find that younger firms use more bank finance in countries with stronger rule of law and better credit information, and that the reliance of young firms on informal finance decreases with the availability of credit information. Overall, the results suggest that improvements to the legal environment and availability of credit information are disproportionately beneficial for promoting access to formal finance by young firms.